Shyness in Broken Home Teenagers - Setiasih, Windi; Saut H. Hutahaean, Erik; Fahrudin, Adi (Rifa'Institute, 2023)
Introduction: Disharmony in the family ends in divorce making the child a victim, shame is an emotional experience that often affects social interactions and psychological well-being of individuals. Teenagers from broken homes face additional challenges in coping with the shame experienced. Objective: This research aims to analyze the self-esteem and feelings of shame among teenagers who come from broken home families The study will involve a sample of adolescents aged 10-19 years from broken home families. Method: Respondents will be selected using non-probability sampling techniques. The research method in this research uses correlational studies through quantitative research methods. Result and Discussion: The level of shame of divorce victims is higher than that of adolescents with harmonious families. High levels of shame result in the self-esteem of broken home teenagers declining. Conclusion: The higher the level of shame felt by teenagers from broken homes, the lower the level of self-esteem possessed by them.